THE SOCIO-ECONOMIC NECESSITY AND STRATEGIC IMPORTANCE OF SHAPING THE ECONOMIC CULTURE OF YOUTH - Maksud Abdimannonovich Nabiyev (Innovate Conferences, 2025)
In today’s globalized world, the sustainable development and competitiveness of each country are closely linked to the level of economic culture among its younger generation. Economic culture of youth refers to their attitudes, knowledge, and skills related to money, financial resources, entrepreneurship, labor, and economic processes in general, as well as their economic behavior. Shaping the economic culture of young people not only ensures their personal well-being but also makes a significant contribution to the socio-economic development of society. This article provides an in-depth analysis of the socio-economic necessity and strategic importance of developing the economic culture of youth.
Keywords: youth, economic culture, social necessity, strategic importance, financial illiteracy, entrepreneurship, investment activity, skilled workforce, sustainable development, education system.